2011
DOI: 10.1073/pnas.1100223108
|View full text |Cite
|
Sign up to set email alerts
|

Mice with behavioral evidence of tinnitus exhibit dorsal cochlear nucleus hyperactivity because of decreased GABAergic inhibition

Abstract: Tinnitus has been associated with increased spontaneous and evoked activity, increased neural synchrony, and reorganization of tonotopic maps of auditory nuclei. However, the neurotransmitter systems mediating these changes are poorly understood. Here, we developed an in vitro assay that allows us to evaluate the roles of excitation and inhibition in determining the neural correlates of tinnitus. To measure the magnitude and spatial spread of evoked circuit activity, we used flavoprotein autofluorescence (FA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
168
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(178 citation statements)
references
References 38 publications
9
168
0
1
Order By: Relevance
“…3), or "far" from the startle elicitor, consistent with the timing used in other studies (e.g., Middleton et al 2011) (see Fig. 8, insets).…”
Section: Prepulse Inhibition (Ppi) Of the Acoustic Startle Is Enhansupporting
confidence: 71%
See 1 more Smart Citation
“…3), or "far" from the startle elicitor, consistent with the timing used in other studies (e.g., Middleton et al 2011) (see Fig. 8, insets).…”
Section: Prepulse Inhibition (Ppi) Of the Acoustic Startle Is Enhansupporting
confidence: 71%
“…Such hyperactivity is measurable within a few hours (Noreña and Eggermont 2003;Salvi et al 2000) and can persist indefinitely, in the absence of further experimental manipulation (Bauer et al 2008;Kaltenbach et al 2000). Neurophysiological studies in vivo and imaging studies in vitro have suggested that decreased inhibition in an early stage of the ascending pathway, for example in dorsal cochlear nucleus (DCN), leads to the "sign change" that underlies the transformation of reduced cochlear nerve output into enhanced central activity (for review, see Roberts et al 2010; see also Middleton et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Significant changes in gene expression were also observed bilaterally in the ICC. These observations compliment studies that explicitly link hyperactivity and tinnitus behavior to inhibitory changes in the DCN (Middleton et al 2011) andICC (Bauer et al 2000). Consequently, the hyperactivity of ICC neurons may reflect both ascending and local influences that interact with independent time courses.…”
Section: Role Of the Vcnmentioning
confidence: 64%
“…According to the hyperactivity model of tinnitus, neurons in the central auditory system respond to the weakened input of a sound-damaged cochlea by down-regulating inhibitory connections (Moller 2007;Middleton et al 2011;Wang et al 2011) and enhancing membrane excitability (Dong et al 2010;Pilati et al 2012;Koehler and Shore 2013;Li et al 2013). This "rebalancing" may raise spontaneous activity (i.e., activity in the absence of sound) to levels that impart a false perception of sound stimulation (Chen and Jastreboff 1995; Kaltenbach and Afman 2000;.…”
Section: Introductionmentioning
confidence: 99%
“…Such changes have been well characterized at the multiunit and single-unit levels in structures as diverse as the dorsal cochlear nucleus (DCN) (Brozoski et al, 2002;Finlayson and Kaltenbach 2009;Kaltenbach and McCaslin 1996;Kaltenbach et al 2000Kaltenbach et al , 2002Middleton et al 2011;Shore et al 2008), the ventral cochlear nucleus (VCN) (Vogler et al 2011), the inferior colliculus (IC) (Bauer et al 2008;Chen and Jastreboff 1995;Dong et al 2009Dong et al , 2010aDong et al , 2010bJastreboff and Sasaki 1986;Mulders and Robertson 2009;Mulders et al 2010Wallhäusser-Franke et al 2003), and the auditory cortex (Eggermont and Kenmochi 1998;Eggermont 2005, 2006;Ochi and Eggermont 1997;Seki and Eggermont 2003;Wallhäusser-Franke et al 1996), suggesting that tinnitus may be a system-wide pathology. Indeed, functional imaging studies in both animals and human subjects with tinnitus show clear evidence of hyperactivation of centers both within and beyond the auditory system (Brozoski et al 2007;Eichhammer et al 2007;Langguth et al 2006;Lanting et al 2008;Lobarinas et al 2008;Lockwood et al 1998;Melcher et al 2000Melcher et al , 2009Reyes et al 2002).…”
mentioning
confidence: 99%